FLA on Toddler's Speech in Minangkabau Language: A Process of Linguistic and Psychological Aspects - Firdaus, Saiyidinal (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
Chomsky (1975) explained that language to children could be through genetic or biological factors. This research discusses the process of the first language acquisition in child aged around 2.5 years in understanding the utterances of his mother tongue (Minangkabau language). In this process, a child's pronunciation imperfection is motivated by sound language mastery and the level of language production that is not yet perfect. Clark (2009) stated that deficiencies in the pronunciation of certain sounds appear when child learn his first language. The purpose of this research is to see and review how the relationship between linguistic aspects in the form of phonological levels and psychological elements in the form of competency and production level of child's utterences in the Minangkabau language. This study uses a qualitative approach with a descriptive analysis process. This research is observed the regional languages ??spoken directly by mothers to her child. The results of the study show that the child dominates the repetition system of the words he heard but still had problems pronouncing and sounding. The output in this study is the repetition system that the child controls has not determined the correct language sound and grammar in first language acquisition in the Minangkabau language